Regression Analysis on the Impact of Agriculture, Industry and Service Sector on Economic Growth in Nigeria - Michael, Ibrahim; Akobi, Clement; Stephen, Mathew (Asian Journal of Science, Technology, Engineering, and Art, 2024)
This study investigates the impact of agriculture, industry, and the service sector on Nigeria's economic growth from 1990 to 2022, using data obtained from the Central Bank of Nigeria (CBN) Statistical Bulletin. Employing an Ordinary Least Squares (OLS) regression model, the research explores the contributions of these key sectors to Nigeria's Gross Domestic Product (GDP). The findings reveal that the industrial sector has a significant positive effect on GDP, emphasizing its crucial role in driving economic growth. The agricultural sector also contributes positively, though its impact is relatively modest, highlighting the need for modernization and investment to enhance productivity. Surprisingly, the service sector shows a statistically significant negative impact on GDP, contrary to its traditionally recognized role in economic expansion. This anomaly suggests underlying structural issues within the sector that require further investigation. The study's model explains approximately 59.65% of the variation in GDP, with no significant evidence of autocorrelation, heteroskedasticity, or multicollinearity affecting the results. Based on these findings, the study recommends targeted policy interventions to improve agricultural productivity, strengthen industrialization efforts, and reform the service sector to foster balanced and sustainable economic growth in Nigeria.